IRF8 is the target of SIRT1 for the inflammation response in macrophages - Yanhui Jia; Shichao Han; Jun Li; Hongtao Wang; Jiaqi Liu; Na Li; Xuekang Yang; Jihong Shi; Juntao Han; Yan Li; Xiaozhi Bai; Linlin Su; et al. (2016)
The type III histone deacetylase SIRT1 has recently emerged as a critical immune regulator by suppressing T-cell immunity and macrophage activation during inflammation, but its mechanism in regulating inflammatory response in macrophages remains unclear. Here we show that the expression of SIRT1 in macrophage cells decreased following the release of inflammation cytokines when the cells were stimulated with LPS. IRF8, an important regulator in monocyte differentiation and macrophage polarization, showed the opposite trend, with SIRT1 expression levels increasing after the cells treated with LPS. Co-immunoprecipitation and immunofluorescence experiments showed that SIRT1 could not only interact with IRF8, but also deacetylate it. LPS treatment had no effect on the expression of IRF8 in macrophage cells in which sirt1 was specifically deleted. Our results show that IRF8 may be the target of histone deacetylase SIRT1 to regulate the inflammation in the macrophage cells.